On the polyamorphism of fullerite-based orientational glasses - Aleksandrovskii, A.N.; Bakai, A.S.; Cassidy, D.; Dolbin, A.V.; Esel’son, V.B.; Gadd, G.E.; Gavrilko, V.G.; Manzhelii, V.G.; Moricca, S.; Sundqvist, B. (Физика низких температур, 2005)
The dilatometric investigation in the temperature range of 2–28 K shows that a first-order
polyamorphous transition occurs in the orientational glasses based on C₆₀ doped with H₂, D₂ and
Xe. A polyamorphous transition was also detected in C₆₀ doped with Kr and He. It is observed that
the hysteresis of thermal expansion caused by the polyamorphous transition (and, hence, the transition
temperature) is essentially dependent on the type of doping gas. Both positive and negative
contributions to the thermal expansion were observed in the low-temperature phase of the glasses.
The relaxation time of the negative contribution occurs to be much longer than that of the positive
contribution. The positive contribution is found to be due to phonon and libron modes, whilst the
negative contribution is attributed to tunneling states of the C₆₀ molecules. The characteristic
time of the phase transformation from the low-T phase to the high-T phase has been found for the
C₆₀–H₂ system at 12 K. A theoretical model is proposed to interpret these observed phenomena.
The theoretical model proposed, includes a consideration of the nature of polyamorphism in
glasses, as well as the thermodynamics and kinetics of the transition. A model of noninteracting
tunneling states is used to explain the negative contribution to the thermal expansion. The experimental
data obtained is considered within the framework of the theoretical model. From the theoretical
model the order of magnitude of the polyamorphous transition temperature has been estimated.
It is found that the late stage of the polyamorphous transformation is described well by the
Kolmogorov law with an exponent of n = 1. At this stage of the transformation, the two-dimensional
phase boundary moves along the normal, and the nucleation is not important.